Fair Traders - Jacusso, Nino (Switzerland : Filmdelights, 2018)
Three free market players take on ethical responsibility and engage in sustainable production. These three pioneers, working in sustainable cotton production, zero-waste fashion and organic farming, balance fair working conditions, biological production and the cost pressures of the free economy day in, and day out. The film examines what a neo-liberal economic model could look like, and presents a motivating approach to solving a situation which often appears hopeless.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films